Visit Intention Model: Integrating Religiosity, Halal Friendly Attributes, Perceived Risk, Perceived Value, Destination Image in West Java - Heru Mulyanto; Anna Wulandari; Samsuri Samsuri (Fakultas Ekonomi dan Bisnis Islam, 2025)
This study aims to examine the influence of religiosity on visit intention in halal tourism, with halal-friendly attributes, perceived risk, perceived value, and destination image as mediating variables. This study contributes to the existing literature by integrating perceived risk, perceived value, and destination image as mediating variables. This study offering a comprehensive understanding of the factors influencing visit intentions in halal tourism.The research employs a quantitative approach using Structural Equation Modeling (SEM) to analyze data collected from 203 tourists in the West Java. The study reveals that religiosity significantly enhances halal-friendly attributes, perceived risk, and perceived value, while halal-friendly attributes positively influence perceived value. Perceived value and destination image are critical determinants of visit intention, whereas perceived risk does not mediate the influence of religiosity and halal-friendly attributes on destination image and visit intention. Tourism stakeholders should focus on strengthening halal-friendly services, enhancing tourists’ perceived value, and building a positive destination image rather than overemphasizing risk mitigation strategies to effectively increase visit intention.